Migration of nutrients and formation of micro/nano-sized particles in Atlantic salmon (Salmo salar) and bighead carp (Aristichthys nobilis) head soups. (August 2020) - Lin, Liu; Tao, Ningping; Su, Hong; Zhang, Jing; Zhong, Jian
Abstract: Atlantic salmon heads (ASH) and bighead carp heads (BHCH) were used to prepare fish head soups. The migration of nutrients and the formation and structure of micro/nano-sized particles (MNP) in the cooking process were studied. With the optimal cooking conditions including a ratio of fish head to water of 1:8 (w/w) and oil-fried 40 s before cooking, nutrients including total lipids, water-soluble proteins, total sugars, total minerals, solids and vitamins in the fish head tissue migrated continuously into the soup. At 150 min, the total lipids, total sugars, and tocopherol in the soup were maximized. After 150 min, the water-soluble proteins, total minerals and solids continued to increase, but there were no significant differences (P ≥ 0.05) between 150 and 180 min. The migration of nutrients from ASH was greater than that from BHCH. An inverted optical microscopy was used to study the formation and changes of the MNP in the fish head soups. From 30 min, the nutrients in the soup had already interacted and self-assembled to form MNP. At 150 min, the most stable bilayer of MNP were formed, and at 180 min, the MNP combined to form larger aggregates. The microscopic structure of the MNP was studied using laser scanning confocal microscopy. Triglycerides self-assembled to form spherical particles, while proteins, phospholipids and glycosylated molecules were distributed on the periphery of the triglyceride globules.